2020
DOI: 10.1371/journal.pone.0230779
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subtypes and transmitted drug resistance strains of HIV among Beijing residents between 2001-2016

Abstract: Background Beijing is a national and international hub potentially containing a broad diversity of HIV variants. Previous studies on molecular epidemiology of HIV in Beijing pooled together samples from residents and non-residents. Pooling residents and non-residents has potentially introduced bias and undermined a good assessment and the intervention among the autochthonous population. Here, we aimed to define HIV subtype diversity and investigate the TDR in Beijing residents exclusively. Methods We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The overall prevalence of TDR is 2.20% in Guangdong. In general, this prevalence has remained low according to WHO categorisation methods [ 34 ], and is lower than that in other regions of China [ 12 16 ]. A significant difference between the prevalence of TDR and CD4 + T cell count and genotype was observed, consistent with previous results [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prevalence of TDR is 2.20% in Guangdong. In general, this prevalence has remained low according to WHO categorisation methods [ 34 ], and is lower than that in other regions of China [ 12 16 ]. A significant difference between the prevalence of TDR and CD4 + T cell count and genotype was observed, consistent with previous results [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, a nationwide cross-sectional survey revealed that the overall prevalence of TDR was 3.6% in China [ 11 ]. More recently, the TDR rate of many cities in China has increased 4.5% in Beijing [ 12 ], 7.21% in Guangxi [ 13 ], 11.1% in Zhejiang [ 14 ], and 7.8% in Tianjin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not realize that the higher CD4 counts could be regarded as a proxy of slower disease progression, nor did they generalize from their finding the conclusion that CRF07_BC progresses slower than CRF01_AE. We have previously shown that CRF07_BC has a lower TDR prevalence than subtype B and CRF01_AE (1.5% vs. 4.8% vs. 5.6%) respectively 27 , 28 . Ge et al 29 and Cao et al 30 have demonstrated that CRF07_BC is associated with better immune recovery in Chinese patients undergoing antiretroviral treatment (ART) compared to that of patients infected with CRF01_AE.…”
Section: Discussionmentioning
confidence: 93%
“…The first group comprised all patients with the HIV TDR genotype, performed between 2001 and 2020 at the BHLN. BHLN is a national collaboration engaged in surveillance of HIV TDR in China 27 , 28 . These methods have been previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation